Development of a Real-Time Multiplayer Web-Based Mathematical Puzzle Game for Geometric Reflection Learning Using WebSocket - Fathan Mohamad; Rahmat Deddy Riyanto Dako; Ulfatun Nadifa; Wahab Musa; Syahrir Abdussamad; Bambang Panji Asmara (Jambura Journal of Electrical and Electronics Engineering, 2026)
Mathematics learning at the senior secondary level often faces challenges related to student engagement, heterogeneous comprehension levels, and the absence of interactive feedback mechanisms. This study develops and evaluates a web-based mathematical puzzle game named "ISOMETRIA" that integrates WebSocket technology to support real-time multiplayer features for learning the reflection topic among Grade XI students at MAN 1 Gorontalo City. The research follows the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The system was built using Phaser.js on the front end and Node.js, Express.js, and Socket.io on the back end, deployed via Vercel and Railway. WebSocket communication is structured into four phases: matchmaking, character selection, map exploration, and battle. A server-authoritative approach with a 200 millisecond race window mechanism was implemented to ensure fair and consistent gameplay under varying network latency conditions. Functionality testing across 25 scenarios confirmed that all features performed as expected. Effectiveness was evaluated with 38 students using a pre-test and post-test design. Mean scores improved from 57.1 to 69.2, and Wilcoxon Signed-Rank Test results yielded p 0.001, indicating a statistically significant improvement. Student response questionnaires returned an average score of 3.58 (sufficient agreement), covering usability, engagement, and perceived benefit. The research results indicate a significant improvement in learning outcomes following the use of the media